Taming polysulfides and facilitating lithium-ion migration: Novel electrospinning MOFs@PVDF-based composite separator with spiderweb-like structure for Li-S batteries. (1st January 2021) - Feng, Yang; Wang, Gang; Kang, Weimin; Deng, Nanping; Cheng, Bowen
Highlights: A novel spiderweb-like MOFs@PVDF-based composite separator was prepared by electrospinning. Membranes present prominent liquid electrolyte absorption ability, structural stability and ionic conductivity. Membranes can inhibit the shuttle effect of polysulfide and suppress lithium-dendrite. Li-S cell with the membrane presents stable long cycle performance and safety. Abstract: Herein, a special spiderweb-like poly (vinylidene fluoride) (PVDF) gel polymer electrolyte (GPE) including tetrabutylammonium chloride (TBAC) and exposed ZIF-8 nanoparticles was prepared via electrospinning technology. Due to the synergy of TBAC and ZIF-8, the prepared ZIF-8@TBAC-PVDF (ZIF@T-PVDF) nanofibers were yielded spiderweb-like structure with gel fibers, small pore size, high porosity and uniformly exposed nanoparticles on the surface, thus improving the absorption capacity of the liquid electrolyte. In particular, the uniform distribution of lithium ions above the lithium anode with the limitation of the spiderweb-like structure facilitates uniform lithium deposition and reduces the generation of lithium dendrites. Moreover, the LSBs with ZIF@T-PVDF membranes exhibited high first-cycle discharge capacity of 1324.2 mAh g −1 with extended cycling stability of 0.05% per cycle and Coulombic efficiency of 97% after the 700 cycles at 2 C. The excellent electrochemical and safety properties are attributed to the fact that the gel-like membrane material can not only physically block and chemically adsorb lithium polysulfides (LiPSs), but also greatly inhibit the growth of dendrites. Therefore, the spiderweb-like ZIF@T-PVDF separator can be identified as a dependable candidate for the advanced LSBs. Graphical abstract: Image, graphical abstract